Bending the Truth in The Bell Jar : Deceitful Communication in the Direct Speech of Esther Greenwood - Salmi, Lotta (My University, 2025)
The aim of this bachelor’s thesis is to analyze the deceitful direct speech of Esther Greenwood in the novel The Bell Jar. Esther Greenwood is the protagonist of the novel, and her dialogue is analysed in terms of honesty. In this thesis Esther’s lies are divided into three categories: self-deception, lying out of politeness and lying out of convenience. A closer attention is paid to the communication between Esther and her former boyfriend Buddy Willard, who in contrary to Esther, appears brutally honest. Grice’s maxims are utilized in the analysis as well as the concept or face, as used by Brown and Levinson in the study of politeness. This thesis implicates that Esther mostly lies out of convenience to make her own life easier, except for when it comes to Buddy. In the relationship Esther appears to observe the norms of politeness and confine to expectations. Interesting further research would investigate the cultural and other reasons behind Esther’s lies.
Keywords: Sylvia Plath, The Bell Jar, autobiography, deceit, lying, face